Programa "A voz do Brasil para Cristo": a relação estabelecida entre o líder pentecostal Manoel de Mello e o rádio - Lima, José Hélio de (2008)
This work present analyses the use of the radio as a mean of communication by the missionary Manoel de Mello, who promoted changes in some of the religious paradigm of the brazilian pentecostalists, turning the church O Brasil para Cristo into the main point between 1950 and 1970. His daily presence at radio programes, that were transmited by radio stations from São Paulo, specially radio Tupi which reached lots of Brazilian cities and some South American countries that have their frontiers with Brazil, made Mello a popular evangelist. On the program A Voz do Brasil Para Cristo he preached for the divine cure, analyzed daily-facts, prayed for the listeners cure who did their requests by calls and letters, and announced the Evangelistic Campaign that was taken place at the whole country. At the beginning of the 50 s the two biggest Brazilian Pentecostal churches were against the radio program, by considering it the devil s instrument. Manoel de Mello innovated the religious section that resulted on lots of retaliations. With his popularity he took his followers and admires from different evangelic associations to choose, by vote, the first pentecostal church congressman. Mello had success when he joined his religious proposal, that faced specially the suburb needy population, with the radio which was the most available mean of communication in Brazil, at that time. These successful undertaking was used as a model for the other Brazilian groups to start on the radio media and sequentially the TV media.